Ten-Year Differences in Nutritional Status and Obesity-Related Risk Factors in Polish Preschool Children - Marcela Zembura; Paweł Lula; Paweł Matusik (MDPI AG, 2023)
The aim of this study was to assess ten-year differences in nutritional statuses and obesity prevalences between populations of preschool children from Katowice, Poland, examined in 2007 and 2017, and to determine factors associated with overweight and obesity in preschool children. A cross-sectional questionnaire was conducted among parents and legal guardians of 276 preschool children in 2007 and 259 preschool children in 2017. Basic anthropometric measurements were performed. Overall, the prevalence of overweight and obesity among our sample of Polish preschool children (median age 5.25 year) was 16.82%, whereas 4.49% of children were obese. No significant differences in the number of overweight and obese children were observed when comparing the years 2017 to 2007. Overall body mass index (BMI) z-score was significantly lower in this group of children from 2017. However, median values of the BMI z-score were higher in two of the weight categories (overweight and obesity) in 2017. The child's BMI z-score was positively correlated with birth weight (r = 0.1, p < 0.05). The BMI z-score was positively correlated with maternal BMI, paternal BMI, and maternal pregnancy weight gain, r = 0.24 p < 0.01; r = 0.16 p < 0.01; r = 0.12 p < 0.05, respectively. A decrease in overweight and obesity prevalence over the past decade and higher median values of BMI z-scores in the group of children with excessive weight in 2017 were observed. Birth weight, maternal BMI, paternal BMI, and maternal pregnancy weight gain all correlate positively with a child's BMI z-score.